NOTCH2 Hajdu-Cheney Mutations Escape SCF(FBW7)-Dependent Proteolysis to Promote Osteoporosis - Fukushima, Hidefumi (Mol Cell, 2017)
Hajdu-Cheney syndrome (HCS), a rare autosomal disorder caused by heterozygous mutations in NOTCH2, is clinically characterized by acroosteolysis, severe osteoporosis, short stature, neurological symptoms, cardiovascular defects, and polycystic kidneys. Recent studies identified that aberrant NOTCH2 signaling and consequent osteoclast hyperactivity are closely associated with the bone-related disorder pathogenesis, but the exact molecular mechanisms remain unclear. Here, we demonstrate that sustained osteoclast activity is largely due to accumulation of NOTCH2 carrying a truncated C-terminus that escapes FBW7-mediated ubiquitination and degradation. Mice with osteoclast-specific Fbw7 ablation revealed osteoporotic phenotypes reminiscent of HCS, due to elevated Notch2 signaling. Importantly, administration of Notch inhibitors in Fbw7 conditional knockout mice alleviated progressive bone resorption. These findings highlight the molecular basis of HCS pathogenesis and provide clinical insights into potential targeted therapeutic strategies for skeletal disorders associated with the aberrant FBW7/NOTCH2 pathway as observed in patients with HCS.